Savings Growth, Loan Growth, Customer Growth, Non-Performing Loans, and Capital Adequacy Ratio on Profitability - Ni Luh Putu Widhiastuti; I Gusti Agung Arista Pradnyani (Universitas Bangka Belitung, 2024)
This research intends to analyze the connection between savings growth, loan growth, customer growth, non-performing loans, and the capital adequacy ratio on profitability. The study was conducted on Village Credit Institutions (LPD) in Denpasar city during the period 2021-2022. The sample was selected using purposive sampling, resulting in a total sample of 34 LPDs (Village Credit Institutions) and 68 observations. The data obtained were analyzed using multiple linear regression analysis. The test results prove that growth in savings has a negative impact with profitability, while growth in loans and capital adequacy ratio have a positive affect with profitability. On the other hand, growth in customers and non-performing loan do not affect profitability. It is suggested to add other variables such as BOPO (Operating Expenses to Operating Income), LDR (Loans to Deposit Ratio), or asset growth.